Raw litter decomposition data from five elevational transects on the southern slopes of Mount Kilimanjaro, Tanzania - Juliane Röder; Roland Brandl (PANGAEA, 2024)
We used litter bags with maize husks (Zea mays L.) to compare decomposition rates in 12 vegetation types along an elevation gradient of 3600 m on the southern slopes of Mt. Kilimanjaro, with pairs of natural and disturbed vegetation types along an elevation gradient of 2300 m, and along a land–use gradient from natural forests, traditional agroforestry/homegardens, grasslands and coffee plantations. For details on study sites, see e.g. Peters et al. 2019 (https://doi.org/10.1038/s41586-019-1048-z), Röder et al. 2017 (https://doi.org/10.1111/btp.12403), or any of the other data sets from the same study sites (https://www.pangaea.de/?q=project:label:KiLi). We used litter bags with maize husks as a standard litter (10 cm exttimes 15 cm, mesh size 4 mm exttimes 4 mm (large) or 20 μm exttimes 20 μm (small)). Standard litter consisted of 5 g ± 0.05 g intact inner leaves of maize husks. The maize husks originated from two fields managed by the same farmer. Husks with visible fungal spots were not used, but we had to assume that all husks were infected. The litter was dried at 72 °C for one week to reduce the effect of microorganisms already present on the husks, and then left in the lab for another 2 to 3 days to adjust to normal air humidity and to assume a stable mass before litter bag preparation. Additional litter bags that were not exposed in the field (control) were used to estimate moisture (8.8 % ± 1.6 % mean ± SD, w/w) and ash content (3.0 % ± 0.31 %) at the time of preparation. Moisture and ash content were used to calculate ash–free organic matter content in the litter samples exposed at the sites. Sub-samples of 2 mg were analyzed for carbon (43 % ± 1.2 %) and nitrogen content (0.29 % ± 0.071 %), resulting in a C:N ratio of 156 ± 30.4. Handling bias was close to zero owing to the soft texture of the husks. In August 2011, we placed 12 litter bags per type (large mesh, large mesh + naphthalene, small mesh) on one site each of the lower six vegetation types and of natural Ocotea forest. We additionally placed litter bags on three sites at higher elevations that were not used in the final set of 60 project sites. We collected 6 bags per type after ca. 5 weeks (between 40 and 46 days) and 6 bags per type after ca. 10 weeks (between 66 and 89 days). In March 2012, at the beginning of the cold wet season, we placed 6 litter bags per type (large mesh, large mesh + naphthalene, small mesh) on each of the 60 study sites along the elevation gradient. Bags were arranged in three blocks to cover site–inherent variation. Owing to logistics at the time of collection, we could not sample two of the Erica forest sites, reducing the total number of litter bags to 3 bag types (treatments) x 3 bags x 2 collecting times x 58 sites = 1044 bags. We collected 3 bags per type and site after ca. 5 weeks (between 34 and 53 days) and 3 bags per type and site after ca. 10 weeks (between 63 and 86 days, Table 1). Unfortunately, at four grassland sites and one site in a coffee plantation, litter bags were destroyed accidentally or intentionally, so we decided to collect all remaining bags from these already after 5 weeks. From one grassland site all samples were lost, reducing the number of sampling sites available for this sampling round to 57. Some more bags were lost, or samples could not be used for analysis (soil contamination, accidents or erroneous documentation during sample processing in the lab), further reducing the number of valid bags. In September 2012, at the beginning of the warm wet season, we placed 3-6 litter bags per type (6 bags: large mesh, large mesh + naphthalene, small mesh; 3 bags: small mesh + naphthalene) per site in two natural and four disturbed vegetation types, i.e. in all sites of the two lower elevation levels. Due to logistical challenges, we could only sample one of five elevation transects. We collected 6 bags per type and site after ca. 10 weeks (between 67 and 84 days). In January 2013, we placed litter bags of all four types on a savanna site for a demonstration and collected the bags after 7 days.